Low-dose radiation: interagency collaboration on planning research could improve information on health effects. (22nd November 2019) - Neumann, John; Cook, Joseph; Chan, Allen
Abstract: In September 2017, the US Government Accountability Office (GAO) issued a report on the scientific basis for federal protections against the harmful effects of ionizing radiation—particularly low-dose radiation, or below about 100 millisieverts (10 rem). The report provided examples of how federal agencies developed and applied radiation protection requirements and guidance for workers and the public and examined the extent to which federal agencies funded epidemiological and radiobiological research on the health effects of low-dose radiation and their efforts at coordination of this research. The report found that agencies collaborated on individual projects on radiation's health effects but did not have a mechanism to coordinate research priorities. Consequently, GAO recommended that the Department of Energy (DOE) lead the development of a mechanism for interagency collaboration related to research on the health effects of low-dose radiation.